2019
DOI: 10.1111/jcpe.13197
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal tissue regeneration after low‐intensity pulsed ultrasound stimulation with or without intra‐marrow perforation in two‐wall intra‐bony defects—A pilot study in dogs

Abstract: Periodontitis is a globally prevalent inflammatory disease characterized by destruction of the tooth-supporting periodontal tissues (i.e. gingiva, alveolar bone, periodontal ligament and root cementum) (Petersen & Ogawa, 2012). In the past four decades, various procedures, including bone grafting, guided tissue regeneration, and the use of enamel matrix derivative and growth factors, either alone or in combination, have been performed to accomplish periodontal regeneration (Reynolds et al., 2015). More recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Frontiers in Bioengineering and Biotechnology frontiersin.org histomorphology revealed increased osteogenesis on the tension side, suggesting that LIPUS promotes the osteogenic differentiation of PDLCs or BMSCs; this is consistent with other published studies (Shirakata et al, 2020;Shobara et al, 2021). Of most interest was the observation that the lateral bone cortex on the pressure side was thickened and compensatory osteogenesis was increased; this is of significance for maintaining the thickness of the pressure side alveolar bone in orthodontic treatment, and is consistent with a previous report (Arai et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org histomorphology revealed increased osteogenesis on the tension side, suggesting that LIPUS promotes the osteogenic differentiation of PDLCs or BMSCs; this is consistent with other published studies (Shirakata et al, 2020;Shobara et al, 2021). Of most interest was the observation that the lateral bone cortex on the pressure side was thickened and compensatory osteogenesis was increased; this is of significance for maintaining the thickness of the pressure side alveolar bone in orthodontic treatment, and is consistent with a previous report (Arai et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…dimension as effectively as other ARP treatments (0.81-1.53 mm; Imber et al, 2021;Shirakata et al, 2010Shirakata et al, , 2020. In the horizontal dimension, no significant differences were found in alveolar width at different levels (1 mm, 3 mm, 6 mm blow alveolar ridge) between MDM and C groups.…”
Section: Discussionmentioning
confidence: 75%
“…In vertical dimension, the VHBD in MDM‐6 m group (1.55 mm) was about 1.19 mm smaller than that in C‐6 m group (2.74 mm). It suggested that MDM might reduce the bone reduction in vertical dimension as effectively as other ARP treatments (0.81–1.53 mm; Imber et al., 2021; Shirakata et al., 2010, 2020). In the horizontal dimension, no significant differences were found in alveolar width at different levels (1 mm, 3 mm, 6 mm blow alveolar ridge) between MDM and C groups.…”
Section: Discussionmentioning
confidence: 99%
“…The treated root canal was sealed with a dental sealing material (IRM; Dentsply Sirona, Milford, DE, USA). An alveolar defect (5×5×5 mm) was surgically created on the extracted sites of each premolar according to previous studies [ 20 21 ] ( Figure 2A and B ). After creation of the alveolar defect, the flap was sutured with 4-0 Vicryl (Ethicon Inc., Somerville, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%